Cellular Senescence in Sarcopenia: Possible Mechanisms and Therapeutic Potential - He, Yongyu; Xie, Wenqing; Li, Hengzhen; Jin, Hongfu; Zhang, Yi; Li, Yusheng (Frontiers in Cell and Developmental Biology, 2022)
Aging promotes most degenerative pathologies in mammals, which are characterized by progressive decline of function at molecular, cellular, tissue, and organismal levels and account for a host of health care expenditures in both developing and developed nations. Sarcopenia is a prominent age-related disorder in musculoskeletal system. Defined as gradual and generalized chronic skeletal muscle disorder, sarcopenia involves accelerated loss of muscle mass, strength and function, which is associated with increased adverse functional outcomes and evolutionally refers to muscle wasting accompanied by other geriatric syndromes. More efforts have been made to clarify mechanisms underlying sarcopenia and new findings suggest that it may be feasible to delay age-related sarcopenia by modulating fundamental mechanisms such as cellular senescence. Cellular senescence refers to the essentially irreversible growth arrest mainly regulated by p53/p21CIP1 and p16INK4a/pRB pathways as organism ages, possibly detrimentally contributing to sarcopenia via muscle stem cells (MuSCs) dysfunction and the senescence-associated secretory phenotype (SASP) while cellular senescence may have beneficial functions in counteracting cancer progression, tissue regeneration and wound healing. By now diverse studies in mice and humans have established that targeting cellular senescence is a powerful strategy to alleviating sarcopenia. However, the mechanisms through which senescent cells contribute to sarcopenia progression need to be further researched. We review the possible mechanisms involved in muscle stem cells (MuSCs) dysfunction and the SASP resulting from cellular senescence, their associations with sarcopenia, current emerging therapeutic opportunities based on targeting cellular senescence relevant to sarcopenia, and potential paths to developing clinical interventions genetically or pharmacologically.